THE EFFECT OF SELF-EFFICACY, TALENT MANAGEMENT, AND CONTINUOUS IMPROVEMENT ON EMPLOYEE ORGANIZATIONAL COMMITMENT PT. INDONESIA EPSON INDUSTRY - Rahmat Hidayat; Alex Zami (Strategic Management Business Journal, 2022)
This research aims to test the influence of self-efficacy, talent management, and continuous improvement on employee organizational commitment of PT Indonesia Epson Industry. Self-Efficacy is an (X1), Talent Management as an (X2), Continuous Improvement as an (X3), and Organizational Commitment is a (Y). The method in this study is quantitative. The population of this research is the workers in Epson Line 151 workers. The sample is 110 people using the way of Slovin and data collection using a questionnaire method. The analysis results used a validity test, reliability test, classical assumption test, multiple linear regression test, t-test, F test, and coefficient of determination. So self-efficacy has no significant effect on the organizational commitment of PT Indonesia Epson Industry. In addition, talent management significantly affects the organizational commitment of PT Indonesia Epson Industry employees. Furthermore, it can also be essential that continuous improvement significantly affects the organizational commitment of PT Indonesia Epson Industry employees. Furthermore, self-efficacy, talent management, and continuous improvement together have a significant effect on the organizational commitment of PT Indonesia Epson Industry employees. JEL Classification: L20, L21, L23